2019
DOI: 10.1002/ppsc.201900093
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Aminooxy‐Functionalized Monolayer‐Protected Gold Clusters for Nonpolar and Aqueous Oximation Reactions

Abstract: Aminooxy (–ONH2) groups are well known for their chemoselective reactions with carbonyl compounds, specifically aldehydes and ketones. The versatility of aminooxy chemistry has proven to be an attractive feature that continues to stimulate new applications. This work describes application of aminooxy click chemistry on the surface of gold nanoparticles. A trifunctional amine‐containing aminooxy alkane thiol ligand for use in the functionalization of gold monolayer‐protected clusters (Au MPCs) is presented. Die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…However, THPC-coated, 1.6 nm-diameter Au NPs did not show a plasmon band over this wavelength range. This indicates the smaller size since it is widely known that the LSPR band disappears for NPs of ∼2 nm in diameter or smaller. ,, …”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…However, THPC-coated, 1.6 nm-diameter Au NPs did not show a plasmon band over this wavelength range. This indicates the smaller size since it is widely known that the LSPR band disappears for NPs of ∼2 nm in diameter or smaller. ,, …”
Section: Methodsmentioning
confidence: 89%
“…This indicates the smaller size since it is widely known that the LSPR band disappears for NPs of ∼2 nm in diameter or smaller. 38,44,49 Microscopic Characterization of Au NPs. The as-synthesized Au NPs were attached to (3-aminopropyl)triethoxysilane (APTES)functionalized glass/ITO (glass/ITO/APTES) electrodes by directly soaking the electrodes into solutions of NPs.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Some of the major challenges in this area of research are: 1) the synthesis of uniform NCs with an appropriate ligand stabilizer that provides good size stability in solution, 2) the ability to attach the NCs to an electrode or other support surface, and 3) the use of a stabilizer with weak enough interactions with the metal NC to allow for high surface metal activity. In most cases, small Au NCs have been stabilized with thiolate ligands . Thiolate ligands bridge Au atoms and lift them out of the cluster surface to form strong (RS‐(Au−SR)n) staple motifs .…”
Section: Introductionmentioning
confidence: 99%
“…In most cases, small Au NCs have been stabilized with thiolate ligands. [22][23][24] Thiolate ligands bridge Au atoms and lift them out of the cluster surface to form strong (RS-(AuÀ SR)n) staple motifs. [25] Chen and coworkers synthesized glutathionecoated Au NCs for use as photosensitizers, for example.…”
Section: Introductionmentioning
confidence: 99%
“…The LSPR peak shifted positive with increasing NS diameter, consistent with their size from 4 nm diameter to 70 nm diameter, 112 while the 1.6 nm diameter Au NSs sample showed no prominent LSPR peak as expected for this size. 178,190 We attached 4 nm to 70 nm diameter Au NSs to aminopropyltriethoxy silane (APTES)functionalized glass/ITO electrodes and to APTES-functionalized SiO2-coated Au TEM grids for SEM and TEM measurements, respectively. Ivanova and co-workers previously showed that the peak oxidation potential (Ep,ox)…”
Section: Resultsmentioning
confidence: 99%